2019
DOI: 10.1093/icesjms/fsz060
|View full text |Cite
|
Sign up to set email alerts
|

Acute impacts of bottom trawl gears on benthic metabolism and nutrient cycling

Abstract: Research on the environmental impacts of bottom fishing gears has focused mainly on structural characteristics of benthic habitats such as faunal composition and the physical features of the seafloor. This study focuses more on functional characteristics by addressing the biogeochemical consequences associated with tickler chain beam trawl and electric PulseWing trawl gears. In June 2017, professional fishermen trawled experimental transects with both types of gears in the Frisian Front area of the North Sea. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
55
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 73 publications
4
55
0
1
Order By: Relevance
“…Resuspension of sediment events are very common in natural water systems, including rivers, estuaries [1], intertidal zones [2], shallow lakes [3,4], and shallow sea areas [5]. Studies have confirmed that the surface sediment is easily resuspended by the dynamic action of wind-waves [6], tides [7,8], storms [9], and human disturbance [10][11][12]. The resuspended sediment entering the water body usually contains a large number of microorganisms, biological debris, residues, granular phosphorus, and other nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Resuspension of sediment events are very common in natural water systems, including rivers, estuaries [1], intertidal zones [2], shallow lakes [3,4], and shallow sea areas [5]. Studies have confirmed that the surface sediment is easily resuspended by the dynamic action of wind-waves [6], tides [7,8], storms [9], and human disturbance [10][11][12]. The resuspended sediment entering the water body usually contains a large number of microorganisms, biological debris, residues, granular phosphorus, and other nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of organic matter due to trawling is of great concern along the continental slope [ 64 ], but has also been reported in continental shelf areas [ 65 , 66 ]. An experimental study of the effect of pulse and tickler chain trawling on biogeochemical processes showed that beam trawling resulted in an immediate decline in benthic community metabolism, with tickler chain trawling exhibiting a stronger effect than pulse trawling [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a comparison of the amount of sediment mobilized in the wake of a tickler chain beam trawl and a pulse trawl, Depestele et al (2016) indeed found a good agreement between the numerical predictions and field estimates. Further support comes from a field study of the biogeochemical impacts of pulse and tickler chain beam by Tiano et al (2019) who showed that tickler chain trawling reduced the sedimentary chlorophyll a by 83% as compared to 43% after PulseWing trawling. The difference is in line with the difference in estimated hydrodynamic drag of the bottom components of pulse and tickler chain beam trawls.…”
Section: Discussionmentioning
confidence: 99%
“…Tickler chains disturb the top layer of the sediment, and may inflict mortality among the benthic invertebrate species Hiddink et al, 2017;Sciberras et al, 2018). In addition, fine sediments may be brought into suspension in the wake of the gear (Lucchetti and Sala, 2012;O'Neill and Summerbell, 2016) affecting bio-geochemical processes in the sediment -water interface (Puig et al, 2012;Tiano et al, 2019). Finally, the heavy weight gear and high towing speed -up to 7.5 knots (Poos et al, 2013) -result in a high fuel use of about 7500 litres per fishing day (Turenhout et al, 2016).…”
Section: Introductionmentioning
confidence: 99%